Biotechnology in space - Ruyters, Günter; Betzel, Christian; Grimm, Daniela (Springer, 2017)
This book summarizes the early successes, drawbacks and accomplishments in cell biology and cell biotechnology achieved by the latest projects performed on the International Space Station ISS. It also depicts outcomes of experiments in tissue engineering, cancer research and drug design and reveals the chances that research in Space offers for medical application on Earth. This SpringerBriefs volume provides an overview on the latest international activities in Space and gives an outlook on the potential of biotechnological research in Space in future. This volume is written for students and researchers in Biomedicine, Biotechnology and Pharmacology and may specifically be of interest to scientists with focus on protein sciences, crystallization, tissue engineering, drug design and cancer research.
Keywords: Biotechnology -- Effect of space flight on.; Space sciences.; elektronické knihy; electronic books